The Impact of Date Production and Industry on Rural Development – An Applied Study of the Oasis Region of Libya (Journal of human and social sciences, 2025)
This study aims to analyze the impact of date production and industry on rural development in the Oasis region of Libya. An electronic questionnaire was distributed, and 35 valid responses were collected from date producers and factory owners. The research employed a descriptive-analytical method, with data analyzed using the SPSS software. The findings reveal that date exports have the strongest influence on rural development, while other factors such as infrastructure, low demand, and production-related challenges showed limited significance. The study concludes that strengthening date exports and providing governmental support are key drivers for achieving sustainable rural development.
Keywords: Date production and industry; Rural development; AlWahat region (Libya; Date exports; Date traders